2021
DOI: 10.1002/jor.24905
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effect of electromagnetic fields and nanomagnetic particles on osteogenesis through calcium channels and p‐ERK signaling

Abstract: Electromagnetic fields (EMFs) are widely used in a number of cell therapies and bone disorder treatments, and nanomagnetic particles (NMPs) also promote cell activity. In this study, we investigated the synergistic effects of EMFs and NMPs on the osteogenesis of the human Saos‐2 osteoblast cell line and in a rat calvarial defect model. The Saos‐2 cells and critical‐size calvarial defects of the rats were exposed to EMF (1 mT, 45 Hz, 8 h/day) with or without Fe3O4 NMPs. Biocompatibility was evaluated with MTT (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 66 publications
(123 reference statements)
0
7
0
Order By: Relevance
“…Zhang et al 42 Wright et al 43 McDonald 46 Miyauchi et al 50 Intracellular signaling pathways Influx of ions within cytosol in response to electrical stimuli can activate calciumcalmodulin-calcinueurin-NFAT, RAS and ERK signaling pathways, which in turn promote transcription of various osteogenic genes Winslow et al 52 Zou et al 53 Wu et al 54 Kim et al 55 Cell surface receptors Some cell surface receptors, such as that for epidermal growth factor (EGF), fibronectin and concanavalin, have been reported to undergo redistribution on the cell membrane, in response to electrical stimuli, which in turn modulates cell adhesion, spreading and migration…”
Section: Electroactive/electrosensitive Components Description Key Re...mentioning
confidence: 99%
See 1 more Smart Citation
“…Zhang et al 42 Wright et al 43 McDonald 46 Miyauchi et al 50 Intracellular signaling pathways Influx of ions within cytosol in response to electrical stimuli can activate calciumcalmodulin-calcinueurin-NFAT, RAS and ERK signaling pathways, which in turn promote transcription of various osteogenic genes Winslow et al 52 Zou et al 53 Wu et al 54 Kim et al 55 Cell surface receptors Some cell surface receptors, such as that for epidermal growth factor (EGF), fibronectin and concanavalin, have been reported to undergo redistribution on the cell membrane, in response to electrical stimuli, which in turn modulates cell adhesion, spreading and migration…”
Section: Electroactive/electrosensitive Components Description Key Re...mentioning
confidence: 99%
“…Indeed, upregulation of TGF‐β expression induced by electrical stimuli via the calcium/calmodulin signaling pathway, appears to play a key role in bone defect healing and regeneration 48 . Besides the calcineurin‐calmodulin‐NFAT signaling cascade, elevated intracellular Ca 2+ levels can also activate the Ras and extracellular signal‐related protein kinase (ERK) signaling pathways that promote transcription of pro‐osteogenic genes such as Runx2 55–57 . Additionally, elevated intracellular Ca 2+ levels can promote cell adhesion by facilitating the binding of integrin to fibronectin, 58 as well as promoting cell migration by activating gelsolin to release more actin 59 …”
Section: Electroactive and Electrosensitive Components Of Bone Tissuementioning
confidence: 99%
“…In addition, our previous study revealed that osteogenesis-related markers were highly expressed in the EMF-exposed Saos-2 cells. Furthermore, in vivo experiments using the rat calvarial bone defect model showed that the EMF-exposed group increased bone mass/volume, mineral density, and bone regeneration in defects compared to the control group [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…A distance-related increase in LDH secretion of cell monolayers has not been described for DBD plasma devices, which could be due to the fact that CAP has various components that have a different effect on cells, such as the production of reactive species or the emission of electromagnetic fields or ultraviolet radiation [ 35 ], which could have different effects at a greater distance. For example, other authors have described the effects of electromagnetic fields or UV light on LDH release [ 36 , 37 ]. It may be that at greater distances, only single components of the plasma affect the cells negatively.…”
Section: Discussionmentioning
confidence: 99%